1994
DOI: 10.1210/jcem.78.4.8157719
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging evaluation of adipose tissue and muscle tissue mass in children with growth hormone (GH) deficiency, Turner's syndrome, and intrauterine growth retardation during the first year of treatment with GH.

Abstract: Measurement of muscle and fat tissue mass by magnetic resonance imaging of the thighs was used to study the metabolic effect of human (h) GH in 23 GH deficiency, 8 Turner's syndrome, and 14 intrauterine growth retardation prepubertal patients. They were evaluated before and 1, 3, 6, and 12 months after the onset of hGH treatment. Seven normal children were followed longitudinally as controls. During hGH treatment, a significant increase in muscle tissue and decrease in adipose tissue cross-sectional areas was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
31
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 34 publications
8
31
0
Order By: Relevance
“…Treatment with GH has seemingly beneficial effects on body composition with increases in muscle mass and decreasing amounts of body fat, as seen during 1 year of treatment and as studied by magnetic resonance imaging (MRI) of the thigh in girls with Turner syndrome (225). Likewise, we found that the FFM increased as determined by DEXA scans during shortterm treatment (2 months) with GH.…”
Section: Effects Of Gh Treatmentsupporting
confidence: 49%
“…Treatment with GH has seemingly beneficial effects on body composition with increases in muscle mass and decreasing amounts of body fat, as seen during 1 year of treatment and as studied by magnetic resonance imaging (MRI) of the thigh in girls with Turner syndrome (225). Likewise, we found that the FFM increased as determined by DEXA scans during shortterm treatment (2 months) with GH.…”
Section: Effects Of Gh Treatmentsupporting
confidence: 49%
“…In fact, the universal reductions of several axes may synergize to form a vicious cycle further perturbing body composition, and suggest that only proper supplementation of not only estradiol (and progesterone), but also testosterone and GH/IGF-I may normalize the hormonal milieu, and thereby body composition. GH treatment in TS girls leads to robust increases in muscle mass and normalizes the amount of body fat (6,37). The distribution of fat and muscle was also discordant with accumulation of both the trunk (a mixture of subcontaneous and visceral FM) and visceral FM determined by DEXA.…”
Section: Discussionmentioning
confidence: 82%
“…The acceleration of linear growth and weight gain appeared to be well balanced as GH treatment did not alter Body Mass Index SDS in any of the treatment groups. GH-induced weight increments are thought to be preferentially directed towards bone and muscle rather than to adipose tissue (17).…”
Section: Discussionmentioning
confidence: 99%